KAJIAN INTERAKSI OBAT PADA PENGOBATAN PASIEN GAGAL GINJAL KRONIS HIPERTENSI DI RSUP SANGLAH DENPASAR TAHUN 2007 - Ngurah Putra Riana Prasetya, A. A.; Raka Karsana, A. A.; Ayu Swastini, Dewa (Jurnal Farmasi Udayana; Vol. 1, No. 1, Tahun 2012, 2013)
A research which observing drug interaction in chronic kidney diseasse hypertension compliance patients in RSUP Sanglah Denpasar has been carried out. This research was carried to find out the number of drug interactions in  chronic kidney diseasse hypertension compliance patients therapy. This research was run descriptively and retrospectively. The studies were done by observing  the adverse effect that may raised from the drug interaction which was used. Furthermore, the research also covered about the management to overcome the problem that raised from each interactions. There are about 20 patients which has been confirmed passed the inclusions and exclusions criteria. The observations which were held literaturely based on Lexi Comp was resulting 16 drug interactions. There was no drug interaction with A and X risk factor found. While, drug interactions of B and C risk factor occurred 37,5% with 6 spesific drug interactions for each. Four drug interactions occurred in D risk factor category, it is about 25%. The studies which were held literaturely  based on Drug.com showed 26 spesific interactios with 7 minor interactions, 18 moderate interactions and 1 major interaction, which in percentage about 26,92%, 69,23% and 3,85% respectively.
Keywords: Chronic Kidney Dissease, hypertension, drug interaction